2021
DOI: 10.3390/microorganisms9061271
|View full text |Cite
|
Sign up to set email alerts
|

Lutzomyia longipalpis Antimicrobial Peptides: Differential Expression during Development and Potential Involvement in Vector Interaction with Microbiota and Leishmania

Abstract: Antimicrobial peptides (AMPs) are produced to control bacteria, fungi, protozoa, and other infectious agents. Sand fly larvae develop and feed on a microbe-rich substrate, and the hematophagous females are exposed to additional pathogens. We focused on understanding the role of the AMPs attacin (Att), cecropin (Cec), and four defensins (Def1, Def2, Def3, and Def4) in Lutzomyia longipalpis, the main vector of visceral leishmaniasis in the Americas. Larvae and adults were collected under different feeding regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 73 publications
(103 reference statements)
1
16
0
Order By: Relevance
“…The modulation of defensin genes also occurred in L. longipalpis, where both of them were reported to be modulated after the parasitic infection. LlDef1 was reduced after L. mexicana [65], and LlDef2 was increased after L. infantum infection [19]. In addition, the P. duboscqi defensin, which is more similar to LlDef2, was increased by L. major infection [18].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The modulation of defensin genes also occurred in L. longipalpis, where both of them were reported to be modulated after the parasitic infection. LlDef1 was reduced after L. mexicana [65], and LlDef2 was increased after L. infantum infection [19]. In addition, the P. duboscqi defensin, which is more similar to LlDef2, was increased by L. major infection [18].…”
Section: Discussionmentioning
confidence: 92%
“…The insect defensins motif six conserved cysteines responsible for intra-chain disulfide bonds [46]. It was also previously reported that the sand fly defensin group was divided into two branches, one containing the L. longipalpis defensin 1, 3, and 4, (LlDef1, LlDef3, and LlDef4) and another containing the LlDef2 and N. neivai defensin 2 [19]. Interestingly, the P. duboscqi defensin was previously shown to be closely related to the black soldier fly Hermetia illucens [47], and in our current analysis, it grouped with the L. longipalpis defensin 2.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations